The Influence of Financial Literacy, Access to Capital, Motivation and Interest in Using E-Commerce on the Performance of MSMEs in Karawang Regency - Rizke Wiliyanti; Venni Avionita; Kamaluddin Rahmat (Eduvest - Journal of Universal Studies, 2025)
This study aims to determine the influence of Financial Literacy, Access to Capital, Motivation, and Interest in Using E-commerce on the Performance of MSMEs. This study is a quantitative research using primary data in the form of questionnaires distributed online  (google form media) and offline (direct interviews with respondents). The sample in this study was determined by the Slovin formula with an error tolerance rate of 10% so that the number of respondents was as many as 300 MSME actors. The collected questionnaires are then tabulated and then processed using the SPSS version 26 application. The results of this study show that access to capital, motivation, and interest in using e-commerce have a positive effect on the performance of MSMEs in Karawang Regency. The better access to capital, motivation, and interest in using e-commerce, the performance of MSMEs in Karawang district will increase. Meanwhile, the Financial Literacy variable has an insignificant relationship with the MSME Performance variable in Karawang Regency. Furthermore, the value of the Adjusted R-Square in this study is 0.618 which means that the variation in the variables of financial literacy (X1), access to capital (X2), motivation (X3), and interest in using e-commerce (X4) can explain 61.8% in the variation in the performance of MSMEs (Y). While the remaining 38.2% is influenced by other factors outside this study that can affect the performance of MSMEs.